2023
DOI: 10.15586/aei.v51i4.867
|View full text |Cite
|
Sign up to set email alerts
|

CTRP3 regulates NF-κB and TGFβ1/Smad3 pathways to alleviate airway inflammation and remodeling in asthmatic mice induced by OVA

Abstract: Background: Asthma is a common illness with chronic airway inflammation. C1q/tumor necrosis factor (TNF)-related protein 3 (CTRP3) plays a vital role in inflammatory response, but its effect on asthma is imprecise. Herein, we analyzed the functions of CTRP3 in asthma. Methods: The BALB/c mice were randomized into four groups: control, ovalbumin (OVA), OVA+vector, and OVA+CTRP3. The asthmatic mice model was established by OVA stimulation. Overexpression of CTRP3 was implemented by the transfection of correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Numerous studies have established asthma as a polygenic disease influenced by both genetic and environmental factors [ 61 , 62 ]. Recent research indicates that abnormal gene expression of SMAD3 and Interleukin 33 (IL-33) is strongly correlated with the onset of asthma [ 63 , 64 ]. Research has demonstrated that SNPs at the Smad3 gene locus are associated with RPL.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have established asthma as a polygenic disease influenced by both genetic and environmental factors [ 61 , 62 ]. Recent research indicates that abnormal gene expression of SMAD3 and Interleukin 33 (IL-33) is strongly correlated with the onset of asthma [ 63 , 64 ]. Research has demonstrated that SNPs at the Smad3 gene locus are associated with RPL.…”
Section: Discussionmentioning
confidence: 99%